Loss of SNAI2 in Prostate Cancer Correlates With Clinical Response to Androgen Deprivation Therapy. (2021) - Cmero, Marek; Kurganovs, Natalie J.; Stuchbery, Ryan; McCoy, Patrick; Grima, Corrina; Ngyuen, Anne; Chow, Ken; Mangiola, Stefano; Macintyre, Geoff; Howard, EN (Enrolled Nurse), Nicholas; Kerger, Michael; Dundee, Philip; et al.
Abstract : PURPOSE: Androgen receptor (AR) signaling is important in prostate cancer progression, and therapies that target this pathway have been the mainstay of treatment for advanced disease for over 70 years. Tumors eventually progress despite castration through a number of well-characterized mechanisms; however, little is known about what determines the magnitude of response to short-term pathway inhibition. METHODS: We evaluated a novel combination of AR-targeting therapies (degarelix, abiraterone, and bicalutamide) and noted that the objective patient response to therapy was highly variable. To investigate what was driving treatment resistance in poorly responding patients, as a secondary outcome we comprehensively characterized pre- and post-treatment samples using both whole-genome and RNA sequencing. RESULTS: We find that resistance following short-term treatment differs molecularly from typical progressive castration-resistant disease, associated with transcriptional reprogramming, to a transitional epithelial-to-mesenchymal transition (EMT) phenotype rather than an upregulation of AR signaling. Unexpectedly, tolerance to therapy appears to be the default state, with treatment response correlating with the prevalence of tumor cells deficient for SNAI2, a key regulator of EMT reprogramming. CONCLUSION: We show that EMT characterizes acutely resistant prostate tumors and that deletion of SNAI2, a key transcriptional regulator of EMT, correlates with clinical response.